2021
DOI: 10.1155/2021/8873383
|View full text |Cite
|
Sign up to set email alerts
|

HLA DR Genome Editing with TALENs in Human iPSCs Produced Immune-Tolerant Dendritic Cells

Abstract: Although human induced pluripotent stem cells (iPSCs) can serve as a universal cell source for regenerative medicine, the use of iPSCs in clinical applications is limited by prohibitive costs and prolonged generation time. Moreover, allogeneic iPSC transplantation requires preclusion of mismatches between the donor and recipient human leukocyte antigen (HLA). We, therefore, generated universally compatible immune nonresponsive human iPSCs by gene editing. Transcription activator-like effector nucleases (TALENs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Particularly, off-target toxicity profiling of CAR-neutrophils with or without loading nanodrugs in infused animals, including cytokine release syndrome, neurotoxicity, and on-target off-tumor toxicities observed in CAR-T cells 57 , are needed, despite the short lifespan of neutrophils. While feasible approaches, such as engineering hypoimmunogenic universal donor hPSCs [58][59][60][61] and banking human leukocyte antigen (HLA)-homozygous hPSC libraries 62 , are readily available to avoid the potential risk of graft-versus-host disease (GvHD), preclinical animal models with an intact immune system is still needed to assess the translational potential of our neutrophil therapeutics. Finally, limited anti-tumor cytotoxicity and extension of animal lifespan of CAR-neutrophil nanodrug therapeutics were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, off-target toxicity profiling of CAR-neutrophils with or without loading nanodrugs in infused animals, including cytokine release syndrome, neurotoxicity, and on-target off-tumor toxicities observed in CAR-T cells 57 , are needed, despite the short lifespan of neutrophils. While feasible approaches, such as engineering hypoimmunogenic universal donor hPSCs [58][59][60][61] and banking human leukocyte antigen (HLA)-homozygous hPSC libraries 62 , are readily available to avoid the potential risk of graft-versus-host disease (GvHD), preclinical animal models with an intact immune system is still needed to assess the translational potential of our neutrophil therapeutics. Finally, limited anti-tumor cytotoxicity and extension of animal lifespan of CAR-neutrophil nanodrug therapeutics were observed.…”
Section: Discussionmentioning
confidence: 99%
“…After 13 days of quadruple gRNAs transfection, Lee et al observed that the gene-edited CD3 + T cells composed 62.1% of HLA-I/II-double-negative cells, while retaining surface phenotype and functionality. However, for generation of universally compatible iPSCs ( 142 ), results concluded that TALEN restriction enzymes had the greatest consistency; they were more maneuverable than ZFNs and had fewer off-target events than CRISPR/Cas 9. Even when stimulated with high concentrations of IFN-γ, TALEN-treated fibroblasts lacked HLA-DR expression, which was maintained within iPSCs generation ( 142 ).…”
Section: Engineering Strategies To Reduce Host-versus-graft (Hvg) Effectmentioning
confidence: 99%
“…However, for generation of universally compatible iPSCs ( 142 ), results concluded that TALEN restriction enzymes had the greatest consistency; they were more maneuverable than ZFNs and had fewer off-target events than CRISPR/Cas 9. Even when stimulated with high concentrations of IFN-γ, TALEN-treated fibroblasts lacked HLA-DR expression, which was maintained within iPSCs generation ( 142 ). HLA-DR knockout remained effective and safe in these therapies, suggesting their potential to modify effector cells to prevent HvG effect in cancer immunotherapy ( 143 ).…”
Section: Engineering Strategies To Reduce Host-versus-graft (Hvg) Effectmentioning
confidence: 99%
“…T cells engineered with TALENs enhance the antitumor efficacy of adoptive immunotherapy [ 9 ]. TALENs have also been applied to edit the genome of human induced pluripotent stem cells (iPSCs), making these cells differentiate into immune cells with potential antitumor activity [ 10 ]. The emergence of the CRISPR/Cas system produced a revolution in gene editing technology.…”
Section: Gene Editing Technologiesmentioning
confidence: 99%